An introduction to the philosophy of methodology - Howell, Kerry E. (Sage, 2013)
This book provides students with a concise introduction to the philosophy of methodology. The book stands apart from existing methodology texts by clarifying in a student-friendly and engaging way distinctions between philosophical positions, paradigms of inquiry, methodology and methods. Building an understanding of the relationships and distinctions between philosophical positions and paradigms is an essential part of the research process and integral to deploying the methodology and methods best suited for a research project, thesis or dissertation.